PENGARUH PUPUK ORGANIK SAMPAH KOTA DAN Gliocladium sp. TERHADAP PERTUMBUHAN DAN HASIL CABE (Capsicum annum L.) PADA ULTISOL ASAL BEKASI - Danapriatna, Nana; Hasyim, Emma Agustien (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2011)
Utilization of a combination of municipal solid waste compost and Gliocladium sp. as decomposing microorganisms in the chili farm business is still a little revealed, although the chilli plants have high economic value. This study revealed the combined effect of organic manure from domestic waste and Gliocladium sp. on growth and yield of chili (Capsicum annum L.). Organic matter can reduce the use of inorganic fertilizers up to 50% with no different yield compared with yield on chili plants use inorganic fertilizer in accordance with recommended dosage